PENGARUH TERAPI BERMAIN (MEWARNAI) TERHADAP TINGKAT STRES PADA ANAK USIA SEKOLAH YANG MENJALANI PHYSICAL DISTANCING DI RW 03 KELURAHAN KEDUNGDORO KECAMATAN TEGALSARI SURABAYA - Galuh Permatasari; Dwi Ernawati; Sapto Dwi Anggoro (Jurnal Kesehatan Mesencephalon, 2021)
Abstract : Physical distancing is an action that used to stop the spread of covid-19 desease. Nowadays, the Physical distancing which is done have the impact of the children psychology problems such as stress. The purpose of this research is to examine the influence of coloring play therapy toward children's stress levels in a school age who is through the physical distancing at RW 03, kedungdoro village, Tegal sari districts, Surabaya city. The type of research was using quasy-eksperimental method with pre test-post control group design approach. The number of samples on this research were 52 children of school age and divided into 26 respondents into the  intervention group and 26 respondents into the control group, by using simple random sampling techniques and questionnaire as a measuring instrument. The data analysis was using Mann Whitney and Wilcoxon Signed Rank Test. The result of this research showed that p value 0,001 (p < 0,05) had an influenced of coloring play theraphy toward children's stress level in a school age who was through physical distancing at RW 03, kedungdoro village, Tegal sari districts, Surabaya city. The implications of this research was to reduced stress in a school age who was through physical distancing by doing the coloring play therapy everyday during 20-30 minutes in a free time.